Strategi Pelestarian Bahasa Talai dan Padisua di Halmahera Barat - Ridwan Ridwan; Nirwana Nirwana (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2016)
This study aims to identify the factors causing the extinction of Talai and Padisua Language as well as to find the right model of their preservation. Through the methods of observation and in-depth interview, it is found that there are four primary institutions that help preserve Sahu language: family, society, school, and government. in addition, Talai language and Padisua language have been preserved through their uses in cultural practices and printed on Gospel translated into Sahu language.